Penerapan Metode Sam’iyyah Syafahiyah dalam Meningkatkan Kemampuan Berbicara Bahasa Arab Siswa Kelas VII H Di MTs Islam Ngruki Sukoharjo - Zulfa Azizah Anwar (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2023)
The Lack of Effective and Enjoyable Learning Methods in the Subject Durusullughoh Al-‘Arabiyyah Volume 1 Has Resulted in Low Student Interest, Response, and Engagement, Impacting the Quality of Arabic Speaking Skills Among Class VII H Students. This study aims to improve the Arabic speaking ability of Class VII H students through the application of the Sam’iyyah Syafahiyah (Audio-Lingual) method in Class VII H at MTs Islam Ngruki Sukoharjo. The research uses a descriptive qualitative method with the research subjects being 26 students of Class VII H at MTs Islam Ngruki. Data collection techniques include observation, interviews, and documentation. The data analysis technique follows three stages: data reduction (using the researcher’s observation results and learning evaluation outcomes), data presentation (by describing the collected data), and drawing conclusions. Data validity was tested using method triangulation and data source triangulation. The research findings and discussion show that there was an improvement in students’ learning evaluation results when using the Sam’iyyah Syafahiyah method. This can be seen from the increase in the class average score, reaching an average of 90.69. Based on this data, it can be concluded that applying the Sam’iyyah Syafahiyah method is indeed highly suitable for Class VII students, as the method offers substantial guidance through repetition, which helps increase both student engagement and teacher creativity in the learning process.